STUDY OF BEHAVIOR MECHANICALLY STABILIZED EARTH WALL (MSE-WALL) WITH SAND ON THE MODEL TEST IN THE LABORATORY - Ainun Mawa'dah Noor (Universitas Lambung Mangkurat, 2021)
Different types of field conditions coupled with rapid technological developments gave birth to innovations in the construction of retaining walls. One type of landslide deterrence construction that began to be developed in Indonesia is the Mechanically Stabilized Earth Wall or often called the MSE wall. The main components of the MSE wall are backfill material, lateral reinforcement and facing panel. In this final project, research will be conducted to observe the behavior of MSE wall systems on a laboratory scale.The study was conducted by planning the innovation of the facing panel form and the variation in the number of reinforcement layers. The variations of reinforcement are 1 layer, 2 layers, 3 layers, 4 layers and without reinforcement. The reinforcement used is sack as a substitute for geotextile woven with selected pile material is sand. In testing the prototype of the MSE wall, a dial gauge is used to find out the deformation, while for loading it uses a jack-push tool.From these tests, the data obtained in the form of shifts, lateral stresses, and the maximum load of the results of the study showed that the application of reinforcement can affect the amount of lateral stress, shifting, and load. The minimum lateral stress is 0.023 kg/cm2 and the maximum load that can be held by the MSE wall is 75 kg.